A Modified k-ε Model for Computation of Flows with Large Streamline Curvature. (14th January 2013) - Yin, Jun-Lian; Wang, De-Zhong; Wu, Yu-Lin; Walters, D. Keith
Abstract : This paper presents an improved method for inclusion of system rotation and streamline curvature effects into existing two-equation eddy-viscosity turbulence models. A new formulation for calculation of the turbulence viscosity coefficient, which is implemented into the traditional k - ε model with a two-layer near-wall treatment in a commercial computational fluid dynamics solver, is proposed. In contrast to precious model, the modified rotation rate which appears in the formulation for turbulent viscosity coefficient is herein expressed exactly and universally. Thus, it provides an effective alternative for turbulence modeling.